2023
DOI: 10.1088/1752-7163/acdf12
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the rationale of mandatory masking

Jonathan D Beauchamp,
Chris A Mayhew

Abstract: In this perspective, we review the evidence for the efficacy of face masks to reduce the transmission of respiratory viruses, specifically severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and consider the value of mandating universal mask wearing against the widespread negative impacts that have been associated with such measures. Before the SARS-CoV-2 pandemic, it was considered that there was little to no benefit in healthy people wearing masks as prophylaxis against becoming infected or as unwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…A scoping review by Kisielinsky et al [34] warns of a CO 2 increase while wearing masks, up to potentially toxic levels, mostly in vulnerable groups; furthermore, Kisielinsky describes a mask-induced exhaustion syndrome with objective measurements [35]. Concurrently with the publication of these hazards, Beauchamp and Mayhew [36] reviewed evidence supporting reduction of SARS-CoV-2 transmission and concluded that the downsides of mask wearing outweigh their potential benefits, both physical and psychological. Additionally, a Cochrane report [37] reviewed the effectiveness of masks to prevent infection, concluding that uncertainty exists regarding the effects of face masks, with pooled results of multiple trials that did not show a clear reduction in spread of respiratory viral infection when using surgical masks.…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review by Kisielinsky et al [34] warns of a CO 2 increase while wearing masks, up to potentially toxic levels, mostly in vulnerable groups; furthermore, Kisielinsky describes a mask-induced exhaustion syndrome with objective measurements [35]. Concurrently with the publication of these hazards, Beauchamp and Mayhew [36] reviewed evidence supporting reduction of SARS-CoV-2 transmission and concluded that the downsides of mask wearing outweigh their potential benefits, both physical and psychological. Additionally, a Cochrane report [37] reviewed the effectiveness of masks to prevent infection, concluding that uncertainty exists regarding the effects of face masks, with pooled results of multiple trials that did not show a clear reduction in spread of respiratory viral infection when using surgical masks.…”
Section: Discussionmentioning
confidence: 99%
“…Additional high-quality data produced throughout the pandemic reinforced that conclusion. In spite of that, with a few exceptions [57], most critical reviews or opinion articles have never questioned the effectiveness of masks in the COVID-19 pandemic. While intuition and laboratory experiments suggest that masks are plausible interventions, their continued failure in randomized clinical trials undermines their effectiveness.…”
Section: Mask In the Lab -Filtering Efficacy As A Secondary Outcomementioning
confidence: 99%
“…Masks should not be mandated for the general population given this balance of evidence against their use. These points have been raised by many scientists [15,17,18,37,38,124,158,165,166] including leading breathing experts [167].…”
Section: Findings In Contextmentioning
confidence: 99%